2022
DOI: 10.1021/acs.est.2c04408
|View full text |Cite
|
Sign up to set email alerts
|

Does Snowfall Introduce Disinfection By-product Precursors to Surface Water?

Abstract: Snow with large specific surface area and strong adsorption capacity can effectively adsorb atmospheric pollutants, which could/might lead to the increase of disinfection by-product (DBP) precursors in surface water. In this study, the contents and characteristics of dissolved organic matter (DOM) in meltwater were investigated, and DBP formation and the DBP-associated cytotoxicity index during chlorination of meltwater was first explored. Overall, meltwater exhibited high nitrogen contents. Meltwater-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…We suspected that small polar water-soluble organic compounds may contribute to the odor events because studies have shown that smaller, polar, and water-soluble organic compounds are released first during snow melts. This led us to investigate AAs, which could leach out first at the beginning of spring runoff when snow starts to melt. AAs may also serve as potential markers of soluble organics that contribute to odor events.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We suspected that small polar water-soluble organic compounds may contribute to the odor events because studies have shown that smaller, polar, and water-soluble organic compounds are released first during snow melts. This led us to investigate AAs, which could leach out first at the beginning of spring runoff when snow starts to melt. AAs may also serve as potential markers of soluble organics that contribute to odor events.…”
Section: Resultsmentioning
confidence: 99%
“…EPCOR has experienced intermittent annual complaints, predominantly about chlorinous issues, for over 30 years. , SHARP is especially useful because it provides timely customer feedback to water treatment plant operators so that informed decisions can be made about taste and odor control measures during critical periods of spring runoff. Temperature increases cause snow and ice to melt, creating runoff with increased debris and organic matter that flows into surface water sources. Most odor complaints in recent years are believed to be attributed to the formation of odorous DBPs arising from precursors that increase during spring runoff. To investigate potential contributors to taste and odor events, we proposed AAs as precursors and as markers of small and water-soluble organics signaling the onset of spring runoff.…”
Section: Introductionmentioning
confidence: 99%
“…6 Disinfectant type (e.g., monochloramine), precursor sources (including amino acids, proteins, amino sugars, amides, nitriles, pyrroles, purines, and pyrimidines), or other organic intermediates (such as hydrazine) have been proven to make great contributions to N-DBP formation. 7,8 However, the possibility of NO 3 − , one of the most common anions in drinking water, as a nitrogen source for N-DBP formation has not been reported to our knowledge.…”
Section: Introductionmentioning
confidence: 94%
“…Though the concentrations of nitrogen-containing disinfection byproducts (N-DBPs) are far lower than those of C-DBPs, N-DBPs potentially pose orders of magnitude greater toxicity than C-DBPs, while brominated and di- and trihalogenated N-DBPs are even more toxic. As N-DBPs, haloacetonitriles (HANs) could be formed in finished drinking water after chlorine disinfection if ammonia or nitrogen-containing organics are present, and HAN concentrations have been observed to be higher in the drinking water distribution system (DWDS) with postchloramination following free chlorination . Disinfectant type (e.g., monochloramine), precursor sources (including amino acids, proteins, amino sugars, amides, nitriles, pyrroles, purines, and pyrimidines), or other organic intermediates (such as hydrazine) have been proven to make great contributions to N-DBP formation. , However, the possibility of NO 3 – , one of the most common anions in drinking water, as a nitrogen source for N-DBP formation has not been reported to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…33 Moreover, snowfall can significantly alter water quality by adsorbing aerosol and organic pollutants on it and allowing them to enter surface water, resulting in a high level of DOM. 34 The wide diversity and large quantity of DBPs that can be formed in drinking water present a daunting obstacle for an explicit understanding of their analysis, occurrence, toxicity, formation, and mitigation. Moreover, with the majority of newer DBPs being present at low levels (ng/L to subμg/L), their detection becomes tedious and requires advanced instrumentation and sophisticated analytical skills.…”
Section: Introductionmentioning
confidence: 99%